2 - LE ROLE DU SECTEUR PUBLIC DANS LA TRANSITION DU SOCIALISME : LE CAS ALGERIEN - M. S. BEDRANI, (Africa Development, 1979)
The Public Sector has always been consïdered as one of the most efficient means for the socialists to transforma capitalist society into a socialist one. Indeed it can help politicians and decision-makers control the whole economy of a country so that it is the people of the country who equally works and equally benefits from their output. Bedrani's article can be roughly ciivided into three parts: 1) - The first partis an account of what iis expected from the 1976 National Charter as far as the Public Sector is concemed. 2) - ln the second part, he tries to show whether the Public Sec tor has reached the objectives which the National Charter set to it. 3) - In conclusion, he found that the Public Sector did not achieve what the National Charter expected from it and even worse, it was crea ting a «Bourgeois» class which is a threat to thEt fundamental principle of socialism. A - The Theory a) - The Algerian socialism as it is contained in the National Char ter. The National Charter is considered as the «supreme source of the policy of the Nation and of Law». In it, Algeria is described as a country in a transition phase towards socialism. The purpose of this future socia- 1.ism is to fight for genuine independence, the abolition of the private pro perty of the means of production as well as the end of the exploitation of rnan byman. b) - The economic role of the Public Sector as given in the Na tional Charter. ln industrial as well as in agricultural matters, the role of the Public Sector is defined in comparison with that of the private sector [n both matters, the Public Sector benefits from much more advantages (the control over the whole industry except for factories dealing with the final phase of the transformation of the products, the allocation of the best fields to the co-operative Public Sector with facilities concerning the implements, seeds etc ...) The Public Sector is the «eye» of the State in industrial and agricultural matters. c) - The Social and Political role of the Public Sector in the Na tional Charter. Politically and soclally the role assigned to the Public Sector is «to get a correct conservation of the people's properties, to en sure regular development of the country in ail its aspects to make the economic, social and political «engine» work according to the rules of efficiency and to the satisfaction of ail, to integrate and adapt itself to the changes continuously brought about by development to see that the principles of social justice on which is founded socialism are respected and fmally to make the workers be the craftsmen of their own destiny. B - The Application Indeed there is a gap between what the National Charter wants the Algerian Socialism to be and what it really is. On the economic plan, the objectives are only partially fulfilled. The objective of food indepen dence which was one of the foremost goals of the National Charter has not been reached because of two reasons: - The population grows quicker than the food production so that the benefits drawn from the selling of hydrocarbon products were spent to import food products. - The technics used were not intensive enough and they did not asso ciate agriculture to animal husbandry. As far as employment was con cemed the authority system forbade the peasants to put up groups moti vated enough to improve the food production. In terms of social and political results, the principles of the Na tional Charter have proved negative in their application because: - The workers and peasa.1ts behaved as wage-earners since they did not feel involved in the making of decisions. - The peasants were interested in the cooperative agricultural sector only in the extent that it gave more facilities for the means of produc tion but they were reluctant to the idea of grouping themselves into co operatives. ln the conclusion, the author says that the Public Sector does not really guarantee the transition ·to socialism. On the contrary the kind of society it is building is capitalist oriented since its development is bighly dependent on technology and foreign investments and that it is creating il new «Bourgeois» class. The main reason for the failure in the policy for il socialist kind of society in Algeria is to be found, according to the au thor, in the fact that there is not a genuine rupture from imperial